(untitled) (Journal of Oriental Studies, 2025)
In the existing database of sources on the history of the Artaxiads and Arsacids, there are minor inclusions that contain information regarding the chronology (duration and sequence) of the reign of the first kings of this dynasty. Information regarding the chronology of the first Artaxiads and Arsacids is scattered across various sources (Greco-Roman, late Babylonian cuneiform, ancient Armenian, ancient Georgian sources). These sources have very different features: the ancient Armenian sources tell us about the number of years of reign, while the Greco-Roman, late Babylonian cuneiform and ancient Georgian sources tell us about the starting points or the end of the reign of a particular king. The article attempts to correct the existing situation, and clarifies this issue using all groups of sources and research literature. Thanks to the involvement of all sources in comparison with the previous conclusions of the research literature, an attempt was made to elucidate this issue and a new chronology of the Artaxiads and Arsacids was presented. The author shows that the information of Movses Khorenatsi, still underestimated at its true worth, is a first-class and trustworthy material in this matter, which not only does not contradict, but, on the contrary, is supported by other sources.